2016
DOI: 10.1371/journal.pone.0162044
|View full text |Cite
|
Sign up to set email alerts
|

Underweight Is an Independent Risk Factor for Renal Function Deterioration in Patients with IgA Nephropathy

Abstract: Studies on the relationship between body mass index (BMI) and renal progression in IgA Nephropathy (IgAN) were limited, especially for underweight patients with IgAN. To elucidate the clinical features and effect of underweight on renal function deterioration in this disease, we recruited IgAN patients with diagnostic age ≥18 years old and a baseline estimated glomerular filtration rate (eGFR) ≥15 ml/min/1.73m2 from our center between 1985 and 2014. Patients secondary to systemic diseases or follow-up less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…Recently, Matsukuma found a J-shaped association between SUA levels and poor renal survival in female patients with IgAN [21]. However, in Matsukuma's study [21], the female patients with the lowest SUA level presented with the lowest level of BMI, which may indicate malnutrition of these subjects that has been demonstrated as an independent risk factor for progression in IgAN [34,35]. In the present study, BMI level in the patients with the lowest quartile of SUA was not significantly lower than that in the patients of the other quartiles.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Matsukuma found a J-shaped association between SUA levels and poor renal survival in female patients with IgAN [21]. However, in Matsukuma's study [21], the female patients with the lowest SUA level presented with the lowest level of BMI, which may indicate malnutrition of these subjects that has been demonstrated as an independent risk factor for progression in IgAN [34,35]. In the present study, BMI level in the patients with the lowest quartile of SUA was not significantly lower than that in the patients of the other quartiles.…”
Section: Discussionmentioning
confidence: 85%
“…The high heterogeneity of prognosis in patients with IgA nephropathy brings difficulties to patient management and treatment. Risk factors were identified, including baseline kidney function, BP, proteinuria, serum albumin, hemoglobin, blood type, body weight, Oxford-MESTC score, and follow-up proteinuria and BP (13)(14)(15)(16)(17)(18)(19). To enhance the predicting accuracy, risk equations were established that showed better performance in predicting prognosis (12)(13)(14)(15)17,19,31).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of IgA nephropathy is highly variable and it is challenging for clinicians to accurately predict kidney outcome at the time of biopsy. Studies on risk factors were carried out and risk models were established by combining independent clinical or pathologic risk factors together to enhance the predictable power of models (12)(13)(14)(15)(16)(17)(18)(19). Most recently, an extended multicenter study developed and validated two risk models by using clinical and Oxford predictors on the basis of Chinese patients with IgA nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI) at either extreme correlates with increased morbidity and mortality in CKD [ 23 25 ]. A Chinese case–control study demonstrated an association between low BMI (< 18.5 kg/m 2 ) and likelihood of end-stage renal disease (ESRD) in IgAN [ 26 ], and a similar Japanese study found patients with elevated BMIs (> 23 kg/m 2 ) had lower rates of proteinuria remission following treatment [ 27 ]. Obesity is postulated to increase proteinuria by inducing ultrastructural changes to the glomerular basement membrane [ 28 , 29 ].…”
Section: Current Approachesmentioning
confidence: 99%